The coopetitive effect in supply chains: exploring the relationship between multiple supply chains from the focal agent perspective - Brandão, Maicom Sergio (Universidade Federal de São Carlos, 2024)
This thesis explores the possibility of a form of interaction between supply chains known as coopetition, which combines cooperation and competition. The main objective is to investigate coopetition among multiple supply chains within an organization from the perspective of supply chain relativism and its implications. This study, organized into six articles, unfolds into two primary streams of inquiry: the perspective of multiple supply chains - resulting in the theoretical framework of the research - and coopetition - providing the basic concepts used in the study. Through a first systematic review, the thesis underscores the significance of the idea of flow as a fundamental concept in understanding the relativism of supply chains, with a particular emphasis on the interaction among material, financial, and information flows. Furthermore, it formalizes the perspective of multiple supply chains as an alternative to the conventional characterization of nodes and links, highlighting the multifaceted nature of supply chain phenomena. Within this vein, it presents the perspective of multiple supply chains as part of organizational discourse from sustainability reports. Besides, the thesis establishes a theoretical framework to investigate coopetition among multiple supply chains. Through a second systematic literature review, it is found that, within the inter-organizational context, there exist various forms of coopetition (technology-based, relationship-based, and channel-based) associated with different supply chains. Through a multiple case study, the execution and cooperative interaction among multiple supply chains are observed, and their similarities and differences concerning inter-organizational coopetition are listed. Finally, through a retrospective case study, it observes how changes in organizational structure can foster the emergence of the distinct supply chains of the organization and shift coopetitive dynamics along the coopetition continuum. The coopetitive effect addressed in this thesis corresponds to interaction founded on a cooperative context occurring among multiple supply chains within an organization - delimited, socialized, and managed by a group of actors - where internal resource scarcity may lead to competition among them. The implications of this interaction can affect not only the focal company but also other links in the supply chain positively or negatively. As contributions, this study proposes that variants of the supply chain term be observed as representatives of the evolution of the research field from the main concepts of phenomenon, orientation, and supply chain management. Considering coopetition, expands the scope of analysis levels to include coopetition among multiple supply chains. Furthermore, the thesis contributes to managerial understanding by proposing strategies to effectively navigate coopetitive dynamics. It emphasizes the importance of identifying core and non-core supply chains, managing power asymmetries among them, and recognizing the role of organizational structure in shaping coopetitive interactions. Additionally, it highlights the importance of mediating elements capable of capturing the global and individual value creation of multiple supply chains. It also underscores the need to differentiate coopetition from a mere supply constraint due to its relational characteristic, thus avoiding tensions and conflicts solely relying on trust among actors to be solved.
O efeito coopetitivo em cadeias de suprimentos: explorando o relacionamento entre múltiplas cadeias de suprimentos a partir da perspectiva do agente focal
Keywords: Cadeia de suprimentos; Terminologia; Coopetição; Múltiplas cadeias de suprimentos; Revisão sistemática da literatura; Estudo de caso; Supply chain; Terminology; Coopetition; Multiple supply chains; Systematic literature review; Case study; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO